Internet-based treatment for depressive symptoms in hemodialysis patients: A cluster randomized controlled trial - Nadort, Els; Schouten, Robbert W.; Boeschoten, Rosa E.; Smets, Yves; Chandie Shaw, Prataap; Vleming, Louis Jean; Dekker, Marijke J.E.; Westerman, Michiel; Hoogeveen, Ellen K.; Bos, Willem J.W.; Schouten, Marcel; Farhat, Karima; et al. (General hospital psychiatry, 2022)
To investigate the effectiveness of a guided internet-based self-help intervention for hemodialysis patients with depressive symptoms. Chronic hemodialysis patients from nine Dutch hospitals with a depression score on the Beck Depression Inventory – second edition (BDI-II) of ≥10, were cluster-randomized into a five modules guided internet-based self-help problem solving therapy intervention or a parallel care-as-usual control group. Clusters were based on hemodialysis shift. The primary outcome depression was measured with the BDI-II. Analysis was performed with linear mixed models. A total of 190 hemodialysis patients were cluster-randomized to the intervention (n = 89) or control group (n = 101). Post-intervention measurement was completed by 127 patients (67%) and more than half of the patients (54%) completed the intervention. No significant differences were found on the BDI-II score between the groups (mean difference − 0.1, 95%CI -3.0; 2.7, p = 0.94). Per protocol sensitivity analysis showed comparable results. No significant differences in secondary outcomes were observed between groups. Guided internet-based self-help problem solving therapy for hemodialysis patients with depressive symptoms does not seem to be effective in reducing these symptoms as compared to usual care. Future research should examine how to best design content and accessibility of an intervention for depressive symptoms in hemodialysis patients. Dutch Trial Register: Trial NL6648 (NTR6834) (prospectively registered 13th November 2017). •Depressive symptoms are highly prevalent in the hemodialysis population•There is need for effective treatment of depressive symptoms in these patients•We investigated the effectiveness of an online self-help PST intervention•No differences were found in outcomes between the intervention and control group•This trial adds to the limited evidence on treatment of depression in HD patients